Perlindungan Hukum Konsumen terkait Pemberian Informasi International Mobile Equipment Identity (IMEI) dalam Pembelian Smartphone Bekas Bermerek Iphone - Dhiya Zahra Wibowo; M Syamsudin (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
This research aims to analyze the fulfillment of the right to consumer information related to the International Mobile Equipment Identity (IMEI) in the purchase of used smartphones branded iPhone and the liability of business actors for losses suffered by consumers. The subject matter studied is legal protection to consumers on the right to IMEI information in buying and selling used smartphones branded iPhone and the responsibility of business actors for losses suffered by consumers related to IMEI blocking in Sleman Regency. The legal research method used is normative using a statutory approach, case approach, and conceptual approach. The type of data required is qualitative data sourced from primary data and secondary data. Data was collected using interviews and literature study. The data was analyzed using a qualitative descriptive analysis method. The results show that consumer legal protection of the right to information in the sale and purchase of used smartphones branded iPhone still does not get adequate legal protection, because consumers do not get correct, clear, and honest information regarding the condition of the goods in accordance with Article 4 letter c of the GCPL Law, causing harm to consumers. Business actors also do not provide full responsibility for the IMEI blocking losses experienced by consumers, seen from the attitude of business actors who actually ask for additional fees and cannot even be contacted when consumers ask for compensation for the losses experienced.